Democratization of Mazhabiyyah and Reconciliation of Politics - Fawaid, Achmad (Universitas Islam Negeri Raden Mas Said Surakarta, 2018)
In the history of Indonesia's struggle to reach its independence, soldiers, scholars, and students had played great roles. Islamic figures such as Ulama' and santri were among those heroes with notable contributions. Although many are not recognized regarding its huge numbers, some has nailed their names nationally for their influential political and religious thoughts. This article tries to explore the political and religious thoughts of Abdul Wahid Hasyim's contribution to the establishment of Islam in Indonesia and the establishment of the Republic of Indonesia. His involvement since the Dutch colonial period, the Japanese occupation, until the independence, shows a santri's struggle for national independence. The result shows that in the context of religion and politics, there are some interesting thoughts delivered by Abdul Wachid Hasyim. His writings on both aspects, religion and politics, predominantly reflect efforts to democratizing different mazhab which led to the modernization of Mazhabiyyah. Wahid Hasyim tried to democratize mazhabiyah differences which previously often cause conflicts and disintegration among Muslims. Wahid Hasyim believes that mazhabiyah differences cannot be obstacles for the unity of the Muslims. On the contrary, these differences can be reformulated to be transformed into a greater concept for the future of Islam. Moreover, he brought about the importance of reconciling political thoughts which can spread unity to the Muslims and Indonesia as a nation. Indonesian Muslims were no longer disintegrated simply due to political issues. He also struggled to reconcile political conflicts involving Muslims and non-Muslims in Indonesia.